INTERNALISASI NILAI-NILAI KARAKTER SISWA PADA PONDOK PESANTREN MADRASAH ALIYAH SYAMSUL HUDA DESA TEGALLINGGAH –SUKASADA-BULELENG-BALI - Moch. Toha Syamsul Arifin; I Nengah Suastika; Dewa Bagus Sanjaya (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2023)
The aims of this study were: 1) To find out the conditions of student character learning at Madrasa Aliyah Syamsul Huda (Masda) Tegallinggah Village, 2) To find out the internalization of student character values ​​at Madrasa Aliyah Syamsul Huda (Masda) Tegallinggah Village. Data on the Internalization of Student Character Values ​​The aims of this study were: 1) To find out the learning conditions of student character at Madrasah Aliyah Syamsul Huda (Masda) Tegallinggah Village, 2) To find out the internalization of student character values ​​at Madrasah Aliyah Syamsul Huda (Masda) Tegallinggah Village. Data on the Internalization of Character Values ​​of Madrasah Aliyah Syamsul Huda (MASDA) Students in Tegallinggah Village, Buleleng were collected through observation, interviews, literature and documentation. Data analysis using descriptive qualitative analysis techniques. The results of the data analysis show that the conditions for student character learning at Madrasah Aliyah Syamsul Huda are going well. Internalization of Character Education Values ​​in Madrasah Aliyah Syamsul Huda students through extra-curricular activities (Scouts, Student Council, PMR,), Singing the Indonesia Raya song, Singing Madrasah Mars, Praying together, Congregational Prayers, and Flag Ceremonies. This shows from the results of research observations, that at Madrasah Aliyah Syamsul Huda there has been a process of systemic internalization of character values ​​both non-academic and academically within the Madrasah Aliyah Syamsul Huda (MASDA) Tegallinggah-Buleleng Village.